The introduction of early patient rehabilitation in surgery of soft tissue sarcoma and its impact on post-operative outcome. Issue 12 (December 2015) - Michot, A.; Stoeckle, E.; Bannel, J.-D.; Colombani, S.; Sargos, P.; Brouste, V.; Italiano, A.; Kind, M.
Abstract: Background: Enhanced recovery after surgery (ERAS) programs are implemented in multiple fields of surgery, but not yet in soft-tissue sarcoma (STS) surgery. We wondered whether its introduction into STS surgery might have impacted postoperative outcome. Methods: Two hundred and fifty seven adult patients with primary limb or trunk wall STS received ERAS from 2008 to 2012 as a part of the intra-operative management. We evaluated, in retrospect, the intra-operative management, post-operative outcomes, functional and oncological results of these patients and compared them with 459 prior patients treated under a standard recovery after surgery (SRAS) program from 1989 to 2007. Results: The most visible change from SRAS to ERAS in the perioperative management was decrease of wound drainage (72% vs. 15%, p < 0.001) and increase of wound bandaging (16% vs. 66%; p < 0.001), underlining the appliance of the ERAS protocol. Post-operatively, hospital stay dropped from nine (0–74) to three (0–22) days (p < 0.001) without affecting major morbidity (8% vs. 5%, NS) or readmission to the hospital (5% vs. 4%, NS). Functional outcome improved (p = 0.009) but whether this change was due to ERAS remains to be proved because complementary treatments changed over time. Tumour control remained unaffected, with an estimated risk of local recurrence at 5 years of 12% in both groups. Conclusion: Introducing a rapid recovery program was associated with a shorter hospitalization stay without compromising surgical or oncological outcomes. The program appears to be safe and reliable to use in patients undergoing STS surgery.